The Effect of Chemical Structure of Newly Synthesized Tertiary Amines Used for the Post Combustion Capture Process on Carbon dioxide (CO2): Kinetics of CO2 Absorption Using the Stopped-Flow Apparatus and Regeneration, and Heat Input of CO2 Regeneration. (July 2017) - Singto, Sudkanueng; Supap, Teeradet; Idem, Raphael; Tontiwachwuthikul, Paitoon; Tantayanon, Supawan
Abstract: This work presents the effect of chemical structure of newly synthesized tertiary amines; 4-(dimethylamino)-2-butanol (DMAB), 4-((2-hydroxyethyl)(methyl)amino)-2-butanol (HEMAB) and 4-((2-hydroxyethyl)(ethyl)amino)-2-butanol (HEEAB) based on the kinetic of the reactions of CO2 absorption in aqueous amine solution in terms of the second-order reaction rate constant ( k 2 ) using the stopped-flow apparatus at 298-313 K and 0.1-1.0 M. The rates and heats of CO2 absorption and regeneration using actual concentrations of single amine and blended amine solvents were also measured respectively at 313 K and 363 K. The results showed that the k 2 of CO2 in amine solutions (i.e. HEEAB and HEMAB) were the first and second highest (1096.9 and 1043.6 m 3 /kmol.s) comparing to DEAB, DMAB and MDEA (47.2, 19.9 and 11.1 m 3 /kmol.s), respectively. Three amines (i.e. HEEAB, HEMAB and DMAB) had fast CO2 absorption rate (0.142, 0.111 and 0.082 mol CO2 /min, respectively) and CO2 regeneration rate (0.295, 0.452 and 0.512 mol CO2 /min, respectively) while maintaining a low heat input of CO2 regeneration (72.44, 60.48 and 39.73 kJ/mol CO2, respectively). The three blended amine solutions (MEA-HEEAB, MEA-HEMAB and MEA-DMAB) at ratio 5:1.25 M all had fast CO2 absorption rates (0.129, 0.108 and 0.094 mol CO2 /min, respectively), CO2 regeneration rates (0.064, 0.072 and 0.070 mol CO2 /min, respectively) and low heat input of CO2 regeneration (188.78, 171.85 and 130.27 kJ/mol CO2, respectively). Based on these results, it was proven that HEEAB, HEMAB and DMAB can be considered to be promising amine components for a post combustion CO2 capture process.